1985
DOI: 10.1051/rnd:19850401
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme potentialities of the abomasum and pancreas of the calf. II. — Effects of weaning and feeding a liquid supplement to ruminant animals

Abstract: Weaning caused a decrease in the chymosin content and an increase in the pepsin content of the abomasum. The amount of chymosin per kg of carcass was on the average 2.8-fold lower and that of pepsin 1.9-fold higher in groups S and SL than in group L. The amount of pepsin tended to be higher in group S than in group SL, but only the difference observed (36 %) for the total amount was significant.In group S, the pancreata showed more chymotrypsin, trypsin and amylase activities but less lipase activity than in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Compared with weaned calves, the relationship of TTSD to FS was inversely related and highly variable in preweaned calves (Figure 1). This result seems logical, as pancreatic production of α-amylase was shown to be low or nonexistent at birth and increased as starch intake increased with age in calves fed milk supplemented with 0.5% corn starch (Huber et al, 1961) or milk replacer with concentrate feed containing 74% corn and 52% starch (Guilloteau et al, 1985). Starter intake was negatively related to MR feeding rates, which was expected given that many studies have observed a reduction in starter intake with increasing MR allowance (Hill et al, 2006a(Hill et al, ,b, 2007Bach et al, 2013).…”
Section: Short Communicationmentioning
confidence: 99%
“…Compared with weaned calves, the relationship of TTSD to FS was inversely related and highly variable in preweaned calves (Figure 1). This result seems logical, as pancreatic production of α-amylase was shown to be low or nonexistent at birth and increased as starch intake increased with age in calves fed milk supplemented with 0.5% corn starch (Huber et al, 1961) or milk replacer with concentrate feed containing 74% corn and 52% starch (Guilloteau et al, 1985). Starter intake was negatively related to MR feeding rates, which was expected given that many studies have observed a reduction in starter intake with increasing MR allowance (Hill et al, 2006a(Hill et al, ,b, 2007Bach et al, 2013).…”
Section: Short Communicationmentioning
confidence: 99%
“…Lee et al (1986) (Kiela et al, 1996). Electrophoretic separation of proteolytic enzymes showed that in the pancreatic juice collected using pouch method the proteolytic enzymes are near fully active or fully active (Gabert et al, 1997 (Guilloteau et al, 1985, Le Dr6an et al, 1997 …”
Section: Exposure Of Duodenal Papillamentioning
confidence: 99%
“…Weaning induces a sharp increase in gastric pepsin and lysozyme activities but a decrease in chymosin activity, which does not disappear in ruminant animals [24,39,75]. In calves, daily quantities of juice, pepsin and electrolytes largely increase; however, those of chymosin decrease [34,44].…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%